Fire-Regulating Services and Disservices With an Application to the Haifa-Carmel Region in Israel - Depietri, Yaella; Orenstein, Daniel E. (Frontiers in Environmental Science, 2019)
In the Mediterranean region, human and economic losses due to forest fires at the urban-wildland interface have increased in the past decades. To counter this trend, economic and human resources are generally invested to combat and suppress wildfires, with much less invested to adapt through ecosystem-based management. Ecosystem services for fire regulation are rarely accounted for in the literature and are generally excluded from ecosystem service classifications. This gap causes fire-regulating services to be overlooked in socio-ecological assessments and in economic valuations, potentially further hampering the design and implementation of ecosystem-based approaches. We review the literature on fire risk reduction related to ecosystem management to define and characterize fire-regulating services and disservices. We then suggest indicators for the assessment of these services and disservices, and we propose a conceptual framework linking fire risk, ecosystem services and ecosystem management practices. In the second part of the paper, we apply these concepts to the historical development of the social-ecological system of the Haifa-Mount Carmel region in Israel, including pre- and post-fire forest management practices. To inform the case study we investigate reports, relevant scientific articles, and policy documents, all corroborated with information from expert lectures on the topic. We conclude by suggesting that human capital should become an integral part of the description and definition of fire-regulating services and disservices, especially for highly modified urban and peri-urban environments.